2019
DOI: 10.29138/prd.v1i1.58
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fashion Lifestyle, Sales Promotion, and Self Image to Impulse Buying Behaviour and Customer Satisfaction

Abstract: This study is to analyze the influence of fashion lifestyle, sales promotion, and self image to impulse buying behaviour and customer satisfaction. Type of research is quantitative. The population of this study were 100 students who used the Shopee mobile application at Narotama Surabaya University. The analysis technique used is Partial Least Square. Data obtained from questionnaires and tasted with SmartPLS 3.0 application. The result of this study indicate that fashion lifestyle, sales promotion, and self i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…The results demonstated that the t-statistic value smaller than t-table and p-value greater than 0.05 can mean that the impulse buying variable as an intervening variable in this study is less able to be a mediator so it cannot strengthen the influence of Beauty Vlogger Review, Self Congruity and Price Perception, which are independent variables of repurchase intention as depen-dent variables. These results are inversely proportional to some previous studies that also use impulse buying as an intervening variable such as research conducted by Mayasari (2019) with the research title "The Influence of Fashion Lifestyle, Sales Promotion and Self Image to Impulse Buying Behavior and Customer Satisfaction", the results Mayasari's research shows that impulse buying has a significant effect and can be an intervening variable for customer satisfaction based on the results of the t-statistic test that is greater than t-table 1,661 and the p-value is smaller than 0.05. Besides Tobing (2019) on the results of his research entitled "The Effect of Utilitarian and Hedonic Shopping Value on Impulse Buying and Its Effect on Repurchase Intention of Fashion Products in Online Stores (Case Study of Online Shopee Consumers in Pontianak)" found that impulse buying has an influence which is significant towards repurchase intention and is able to be a mediator between the independent and dependent variables.…”
Section: Indirect Influencesupporting
confidence: 51%
“…The results demonstated that the t-statistic value smaller than t-table and p-value greater than 0.05 can mean that the impulse buying variable as an intervening variable in this study is less able to be a mediator so it cannot strengthen the influence of Beauty Vlogger Review, Self Congruity and Price Perception, which are independent variables of repurchase intention as depen-dent variables. These results are inversely proportional to some previous studies that also use impulse buying as an intervening variable such as research conducted by Mayasari (2019) with the research title "The Influence of Fashion Lifestyle, Sales Promotion and Self Image to Impulse Buying Behavior and Customer Satisfaction", the results Mayasari's research shows that impulse buying has a significant effect and can be an intervening variable for customer satisfaction based on the results of the t-statistic test that is greater than t-table 1,661 and the p-value is smaller than 0.05. Besides Tobing (2019) on the results of his research entitled "The Effect of Utilitarian and Hedonic Shopping Value on Impulse Buying and Its Effect on Repurchase Intention of Fashion Products in Online Stores (Case Study of Online Shopee Consumers in Pontianak)" found that impulse buying has an influence which is significant towards repurchase intention and is able to be a mediator between the independent and dependent variables.…”
Section: Indirect Influencesupporting
confidence: 51%
“…Perusahaan harus mengaktualisasikan keinginan konsumen menjadi suatu kepuasan yang diberikan melalui produk yang dihasilkan dengan tujuan membangun hubungan baik dengan konsumen sehingga menjadi loyal terhadap perusahaan. Penelitian terdahulu yang dilakukan oleh Susanty & Kenny (2015) serta Mayasari (2019) membuktikan bahwa adanya pengaruh positif dari gaya hidup konsumen terhadap tingkat kepuasan yang dirasakan oleh konsumen. Berdasarkan uraian tersebut, maka hipotesis pertama pada penelitian ini adalah: H1: Gaya Hidup Berpengaruh Positif terhadap Kepuasan Konsumen…”
Section: Hipotesis 221 Pengaruh Positif Gaya Hidup Terhadap Kepuasan ...unclassified
“…According to Mayasari (2019), more impulsive buying behavior occurred with the increase of sales promotions. Previous research (Ismail and Siddiqui, 2019;Kumar and Kaur, 2018;Akram et al, 2017) revealed that sales promotion positively impacted customers' impulsive buying behavior.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In addition, sales promotions offered by e-commerce, such as discounts, free samples, etc. could also influence consumers to have impulsive buying behavior (Mayasari, 2019;Ismail and Siddiqui, 2019;Fitri, 2018;Kumar and Kaur, 2018;Liyanage and Wijesundara, 2020). According to Genchev and Todorova (2017), sales promotion could retain and captivate consumers because it could benefit them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation